Can the Griffiths scales predict neuromotor and perceptual-motor impairment in term infants with neonatal encephalopathy?. Issue 7 (21st June 2004) - Barnett, A L; Guzzetta, A; Mercuri, E; Henderson, S E; Haataja, L; Cowan, F; Dubowitz, L
Abstract : Aims: To examine the predictive value of early developmental testing for identifying neuromotor and perceptual-motor impairment at school age in children with neonatal encephalopathy (NE). Methods: Eighty full term infants with NE were followed longitudinally. Where possible, children were tested on the Griffiths scales at 1 and 2 years and at 5–6 years, on the Touwen Examination, Movement ABC, and WPPSI. The relation between the Griffiths scores and later outcome measures was examined using correlation coefficients and sensitivity and specificity values. Results: By 2 years, 25 children with cerebral palsy were too severely impaired to be formally assessed and remained so at 5–6 years. Abnormal Griffiths scores were obtained by 12% and 7% of the children at 1 and 2 years respectively. At 5–6 years, 33% had poor Movement ABC scores and 15% poor WPPSI scores. The highest correlation between Griffiths scores and the outcome measures was for the Movement ABC (0.72), although this accounted for only 50% of the variance. Sensitivity scores for the Movement ABC were below 70% but specificity was 100%. Conclusions: A poor score on the Griffiths scales at 1 and/or 2 years is a good predictor of impairment at school age. However, a normal score in the early years cannot preclude later neurological, perceptual-motor, or cognitive abnormalities.